Topological Dirac semi-metals as novel, optically-switchable, helicity-dependent terahertz sources - Boland, JL; Xia, CQ; Damry, DA; Schonherr, P; Prabhakaran, D; Herz, LM; Hesjedal, T; Johnston, MB (IEEE, 2022)
The generation and control of terahertz pulses is vital for realizing the potential of terahertz radiation in several sectors, including 6G communication, security and imaging. In this work, we present the topological Dirac semimetal cadmium arsenide as a novel helicity-dependent terahertz source. We show both broadband (single-cycle) and narrowband (multi-cycle) terahertz pulses upon near-infrared photoexcitation at oblique incidence. By varying the incident angle of the photoexcitation pulse, control of the emission frequency can also be achieved, providing a candidate for a tuneable narrowband terahertz source.